Mortality from External Causes in the State of Paraná and the Municipality of Foz de Iguazú, 1996 to 2016. - Duarte Zoilán, Derlis Gustavo Adolfo; Gamarra, Carmen Justina (Medicina Clínica y Social, 2022)
Introduction: External Causes (EC) of morbidity and mortality are identified as intentional injuries (homicides, violence, suicides, deprivation or negligence) and unintentional injuries (transport accidents, drowning, falls, burns, accidental poisoning, complications of medical assistance, among others). Objective: to analyze the cases of mortality due to external causes in the State of Paraná and Municipality of Foz do Iguaçu in the period from 1996 to 2016. Methodology: a quantitative, observational, descriptive ecological, retrospective study was conducted where the deaths due to external causes were analyzed in the State of Paraná and Municipality of Foz do Iguaçu in the period from 1996 to 2016 among men and women. From secondary data available in the Informatics Department of the Unified Health System (DATASUS). Results: The trends in mortality from external causes in the period from 1996 to 2016 in the State of Paraná was stable and in the Municipality of Iguaçu showed decrease; the average in mortality rates of 8.7 and 12.4 per 10,000 inhabitants for Paraná and Foz do Iguaçu respectively. The most important causes of death at the beginning of the study were assaults and traffic accidents for both Paraná and Foz do Iguaçu, with higher rates in ages 15 to 29 years in both sexes, with a difference at the end of the study where the first cause of death in men is assaults with higher rates in ages 15 to 29 years and other injuries due to accidents in women aged 60 years and over. Conclusion: In the 21 years of studies, men represent the highest rate of deaths due to external causes. Mortality rates for deaths due to external causes continue to be alarming for the State of Paraná and mainly for Foz do Iguaçu.
Keywords: Mortality; External causes; Collective Health; Epidemiology.